Changes in Accounting Estimates for Disclosure Discrepancy in The Useful Life of Pot Reduction: Study Case in PT. XYZ (Persero) Indonesia - Deddy Kurniawansyah; Nelly Romauli Simamora (International Journal of Applied Business and International Management, 2023)
This study aims to obtain empirical evidence of the application of changes in accounting estimates to change the useful life of the reduction pot at PT. XYZ (Persero) based on PSAK 25. Data collection techniques used in this study included interviews, observation, and documentation techniques. After the data and information were obtained, data analysis was carried out using qualitative analysis techniques using the Milles K. Hubertman model. The results show that the application of changes to the estimated useful lives of reduction pots results in an increase in depreciation expense in 2021 of USD 2,025,260, and a total of 44 reduction pots will be written off in full at net book value because they have experienced depreciation for or more than 5 (five) years, amounting to USD 1,004,663. The implementation of PSAK 25 has an impact on profit for the year and asset impairment in 2021.